The Influence of Work Stress and Organizational Culture on the Financial Management of PT Food Station Tjipinang Jaya (Perseroda) - Romaito Gea, Pricilia; Ludfi Arifin, Antoni (Dinasti Publisher, 2025)
The Effect of Job Stress and Organizational Culture on Employee abilty at the PT Food Station Tjipinang Jaya (Perseroda). This research aims to determine and analyze the effect of job stress and the effect of organizational culture on the at the Gowa Regency Regional Financial Management PT Food Station Tjipinang Jaya (Perseroda). Data collection used primary data obtained from questionnaires and documentation from 50 respondents, employees of the Regional Financial PT Food Station Tjipinang Jaya (Perseroda.This sample is a saturated sample which makes the total population the total sample size. The results of the questionnaire have been tested for validity and reliability, and classical assumptions in the form of normality, heteroscedasticity and multicollinearity assumptions have also been tested. . The sampling technique used in this research is Nonrandom Sampling. The data analysis technique used is multiple regression and based on the results of the analysis it is concluded that there is a partial positive and significant influence of work discipline on employee performance with a tcount of 2.724 and a ttable of 1.993 or 2.724 > 1.993 and a significance of 0.008 < 0.05. There is a partial positive and significant influence of work stress on employee performance with a tcount of 8.140 and a ttable of 1.993 or 8.140 > 1.993 and a significance of 0.000 < 0.05. There is a positive and significant influence of work discipline and work stress simultaneously on the performance of employees of PT Nitto Materials Indonesia, this is shown by the F test which can get an F value of 79.761 with a significance of 0.000 or 79.761 > 3.12, a significant 0.000 < 0.05. The magnitude of the influence of discipline and work stress can be seen by the coefficient of determination. The customized R square value obtained is 0.680.